Application of external drugs comprising silver compounds for the treatment of pyodermic patients - A. V. Samtsov; I. N. Telichko; A. V. Statsenko; V. R. Khairutdinov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
An external anti-bacterial therapy is selected for pyodermic patients empirically. Silver sulfathiazole has an evident anti-inflammatory and anti-microbial effect against a broad range of microorganisms. Goal of the study. To assess the efficacy, safety and tolerability of a cream comprising 2% silver sulfathiazole vs. 3% tetracycline ointment for the treatment of pyodermic patients. Materials and methods. The study involved 50 pyodermic patients (at the mean age of 23.5 ± 4.1 years) including 31 (62%) male and 19 (38%) female patients. The patients were divided into two groups: Group I (n = 35) used the cream comprising 2% silver sulfathiazole while Group II (n = 15) was administered 3% tetracycline ointment. All of the patients were assessed for clinical and microbiological efficacy of the therapy. Results. The average patient recovery time in Group I amounted to 8.7 ± 0.9 days and 13.1 ± 2.7 days in Group II (р < 0.01). As many as 33 patients (94.3%) achieved clinical recovery and 2 patients (5.7%) achieved improvement by Day 10 in Group I; in Group II, clinical recovery was observed in 8 patients (53.3%), improvement - in 3 patients (20%), and no effect - in 4 patients (26.7%). Conclusion. The external anti-bacterial monotherapy of pyodermic patients with the cream comprising 2% silver sulfathiazole is more efficient than treatment with 3% tetracycline ointment. High clinical and microbiological efficacy of the cream comprising 2% silver sulfathiazole makes it possible to recommend it for empirical treatment of pyodermic patients.